Anti-Scl-70 antibodies detected by immunoblotting in progressive systemic sclerosis: specificity and clinical correlations. Issue 12 (December 1989) - Aeschlimann, A; Meyer, O; Bourgeois, P; Haim, T; Belmatoug, N; Palazzo, E; Kahn, M F
Abstract : One hundred and forty five serum samples from patients with a connective tissue disease and 30 serum samples from healthy blood donors were analysed by immunoblotting. The presence of anti-Scl-70, which seems to discriminate between progressive systemic sclerosis (PSS) and the CREST (calcinosis, Raynaud's phenomenon, esophageal dysmotility, sclerodactyly, telangiectasia) syndrome, was found in 31/64 (48%) patients with PSS, in 6/55 (11%) patients with systemic lupus erythematosus, in 2/26 (8%) patients with mixed connective tissue disease, and in none of 30 healthy blood donors. These data resulted in a specificity of 93% for this antibody in systemic sclerosis. For patients with PSS the duration of disease was significantly shorter in those with anti-Scl-70 antibodies than in those without, whereas the presence of anti-Scl-70 did not correlate with severity of disease. An 82% prevalence of anticentromere antibodies in patients with the CREST variant compared with a 4% prevalence in patients with PSS or with overlap syndrome confirms the high diagnostic value of this autoantibody for the CREST variant of PSS.